Assessment of Impact of Dietary Patterns on Obstructive Sleep Apnea Patients - Gunes, Fatma Esra; Agan, Kadriye; Aktac, Sule; Karadeniz, Derya; Sunter, Gulin; Vural, Ezgi; Benbir-Senel, Gulcin (Sleep Science, 2024)
Objective Obstructive sleep apnea syndrome (OSAS) is characterized by episodic cessations of breathing due to upper airway obstruction during sleep, which may cause disturbances in dietary patterns resulting from appetite-related hormonal changes. The aim of the present study was to investigate the relationship between OSAS and nutritional and dietary patterns.Materials and Methods A total of 20 female and 53 male OSAS patients aged > 30 years were enrolled. Demographic data, as well as data on smoking and alcohol habits, were noted, anthropometric measures were made, and a questionnaire regarding chronic diseases including OSAS and four questionnaires on recent food intake frequency and content of nutrition were filled out. The content of nutrition was noted under seven categories: meat, legumes, milk and dairy products, fruits and vegetables, bread and cereals, fat and carbohydrates, and beverages.Results The severity of OSAS (assessed by the apnea-hypopnea index. AHI) was positively correlated with the body mass index (BMI), the circumferences of the waist, chest, and buttocks, and, in males, with the circumference of the neck as well. There was no correlation between the AHI and nutritional habits in terms of the frequency of meals or snacks, the scores on the Snoring, Tiredness, Observed Apnea, and High Blood Pressure-Body Mass Index, Age, Neck Circumference, and Gender (STOP-BANG) Questionnaire and the corresponding macro- and micronutrients. Worsening apnea scores led to increased intake of macronutrients of carbohydrate and protein and micronutrients of niacin and pyridoxine (p < 0.05), and decreased intake of fat (p < 0.05).Conclusion The present study demonstrated an association between OSAS severity and recent food intake, manifested in increased intake of carbohydrates, niacin, and pyridoxine, and decreased fat intake.
Keywords: obstructive sleep apnea syndrome; body mass index; food analysis; diet